Fatigue Life Prediction for Automobile Coil Spring Using Modal Analysis - Nya, R. Manouchehry; Abdullah, S.; Singh, S.S.K.; Thamburaja, P. (International Journal of Engineering and Technology, 2018)
The aim of this paper is to predict the fatigue life models for a coil spring in vehicle suspension system, which it is a vital part of ground vehicles due to the deflection of the spring is big and continuous. Natural frequencies and mode shapes as known the modal parameters that fatigue life assessment considered as an obstacle in vehicle suspension systems. The finite element analysis performed to obtain the original, mode 1, 2 and mode 3 strain time histories based on the first three modal analyses at each critical area. The objective of this research, to predict the fatigue life in coil spring when it is subjected to free vibration via the hit potholes or bump from any road surfaces. The material design is important to assess the fatigue life, so it has been chosen from the chromium steel, SAE5160 in order to apply frequently in the construction of coil springs. The inverse Fourier transform technique has been utilised in order to produce the strain time history from the power spectral density function. The results show the original and mode 3 signals with amounts of 4.352Â and 67.6 cycles have a good agreement with the Morrow model, whereas mode 1 and mode 2 signals indicate 3.7x10-6 and 2.202x105 values in good agreement with the Coffin-Manson model respectively.